Pengaruh Hubungan Antar Individu dan Penempatan kerja Terhadap Efektivitas Kerja melalui Koordinasi: Studi Kasus pada Pegawai Badan Pengelolaan Keuangan dan Aset Daerah Kabupaten Empat Lawang - Gading, Aptriko; Basyith, Abdul; Syah, Lin Yan (Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2025)
Interpersonal relationships are interactions between individuals with other individuals or groups, which involve human relationships, aimed at achieving satisfaction for both parties. The sample in this study, namely all employees of the Financial and Regional Asset Management Agency of Empat Lawang Regency, as many as 70 people will be used as samples in this study. The independent variables are Interpersonal Relationships (X1) and Job Placement (X2), while the dependent variable is Work Effectiveness (Y). The results of the study obtained (1) Interpersonal Relationships were not proven to have a direct and positive effect on Work Effectiveness at the BPKAD of Empat Lawang Regency. (2) Job Placement was proven to have a direct and positive effect on Work Effectiveness at the BPKAD of Empat Lawang Regency. (3) Coordination was proven to have a direct and positive effect on Work Effectiveness at the BPKAD of Empat Lawang Regency. (4) Interpersonal Relationships were proven to have a direct and positive effect on Coordination at the BPKAD of Empat Lawang Regency. (5) Job Placement was proven to have a direct and positive effect on Coordination at the BPKAD of Empat Lawang Regency. (6) Interpersonal Relationships were proven to have a direct and positive effect on Work Effectiveness through Coordination at the BPKAD of Empat Lawang Regency. (7) Job placement has been proven to have a direct and positive influence on work effectiveness through coordination at the BPKAD Empat Lawang Regency